Ny arkitektur for nordmenn i Iowa. Arkitekt C.H. Griese, Luther College og kirker i 1860-årene - Jens Christian Eldal (Nordlit: Tidsskrift i litteratur og kultur, 2015)
The Norwegian Evangelical-Lutheran Church in America decided in 1861 to build their first college close to the western frontier of The Upper Midwest. The site chosen was a bluff above Upper Iowa River, highly visible from Decorah, a small town founded only 12 years earlier, few years after the first settlers arrived. The college building became a relatively vast structure erected between 1862 and 1865, completed to its originally planned symmetrical composition in 1874. The building style and its composition were common among American colleges and universities further east in the US. It is also demonstrated how the Luther College building façade in composition and detailing shows clear influences from a specific German building. This particular building has been designated as especially typical of the German Rundbogenstil (Style of the Rounded Arch) with its great mix of various stylistic elements.